Pengetahuan Masyarakat Tentang Tanda Bahaya Kehamilan Dengan Memberdayakan Masyarakat Dalam Mendeteksi Secara Dini di Kelurahan Ladang Bambu Kecamatan Medan Tuntungan - Manurung, Nurdiana; Fitri, Sari Rahma (Indonesian Journal Publisher, 2023)
Maternal mortality can occur during pregnancy, childbirth or postpartum. Maternal deaths in Indonesia are caused by 3 late and 4 too. One of the late factors is the delay at the family level in recognizing danger signs in pregnancy, childbirth and postpartum. Early detection of risk factors is necessary to reduce maternal and fetal mortality and morbidity. This is where the role of health workers in early detection of danger signs. This study aims to improve the ability of health cadres in early detection and referral of high-risk pregnancy, labor and postpartum cases. The research method used analytic research. Early detection of pregnancy danger signs by families and recognizing risk factors and complications, as well as appropriate treatment by health workers is the best way to reduce MMR and IMR. The targets of this activity were health cadres and pregnant women, 35 respondents were obtained in Kelurahan Baru Ladang Bambu, Medan Tuntungan Subdistrict. The interventions carried out in this activity were counseling, discussion, and simulation. The measuring instrument used pretest and posttest questionnaires. Data were analyzed using Wilcoxon test analysis. The results of the activity are an increase in the knowledge of cadres and pregnant women about the detection of danger signs of pregnancy, antenatal services provided can obtain data on the condition of their pregnancy and become information for pregnant women until now is still high.